THE IMPLEMENTATION OF THE PLN MOBILE APPLICATION TO IMPROVE SERVICE DELIVERY AT PT PLN (PERSERO) AMUNTAI CUSTOMER SERVICE UNIT - Mardila, Mardila; Agustina, Eka Santi (PPPM STIA Amuntai, 2025)
This research is motivated by a new innovation from the company PT PLN (Persero), namely creating an application called PLN Mobile which was released in 2016 to coincide with the 71st national electricity day and became part of PT PLN's (Persero) efforts to improve services to customers. With the innovation of the PLN Mobile application, it can also bring PLN closer to customers and prospective customers to be much better. The information that can be accessed in this application can also be said to be quite good issn providing services regarding various kinds of information listed in the features in the PLN Mobile application, so that customers can access information anywhere and anytime. This is what makes researchers interested in conducting reseach with the title “Implementation of the PLN Mobile Application in Improving Sevices at PT PLN (Persero) ULP Amuntai” ti find out the problems and solutions that occur in the field. This research uses a qualitative approach method, and data is collected using direct interview techniques, telephone interviews and WhatsApp chat and Google Form. The respondents involved in this study were 6 people with 8 questions from 8 indicators, namely implementation (transmission, clarity, and consistency) service (reliability or reliability, responsiveness or responsiveness, assurance or assurace, empathy or empathy, and physical evidence or tangible). The results of the study show that the implementation of the PLN mobile application does have an effect on improving services at PT PLN (Persero) and making it easier for customers to receive all forms of service. However, it is still lacking in terms of socialization to the community.